Greenland, view of Kjerulf Fjord through to Dicksons Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. Right Valley (general direction east and west). In background on right of photo is eastern terminal of range of mountains on the north side of valley. In foreground stream of Left Valley; above it on left of photo the base of L.A.B.'s Curry-comb Peak, at its northern most point -- where the range to which it belongs turns, goes in a westerly direction and forms the south side of Left Valley. For source of streams see photos: 24-F-11; 24-F-12; 24-F-5; 27-1-13 & 27-1-12. Photo taken from eastern side of Left Valley looking W.N.W.